2018
DOI: 10.1097/md.0000000000011138
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of neutrophil-lymphocyte ratio, lymphocyte-monocyte ratio, platelet-lymphocyte ratio, and mean platelet volume in healthy adults in South Korea

Abstract: There is a growing interest in research aimed at better understanding the disease status or predicting the prognosis of patients with simple blood tests associated with systemic inflammation. The neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR), platelet-lymphocyte ratio (PLR), and mean platelet volume (MPV) can be used as factors to determine the prognosis of patients in various clinical situations. However, reference values for these attributes based on large, healthy populations have yet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
10
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(200 citation statements)
references
References 15 publications
10
152
10
5
Order By: Relevance
“…NLR showed a quadratic relationship with age, such that NLR was highest in chimpanzees between 25 and 35 years old, and was lower in both young and old individuals. This is in contrast with some findings in humans, which show that NLR increases linearly with old age in healthy populations, suggesting increased risk for inflammation [1, 3, 6]. The most parsimonious explanation for these data may be that chimpanzees with lower NLRs reach older ages precisely because they maintain better health, and thus, have lower NLR values.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…NLR showed a quadratic relationship with age, such that NLR was highest in chimpanzees between 25 and 35 years old, and was lower in both young and old individuals. This is in contrast with some findings in humans, which show that NLR increases linearly with old age in healthy populations, suggesting increased risk for inflammation [1, 3, 6]. The most parsimonious explanation for these data may be that chimpanzees with lower NLRs reach older ages precisely because they maintain better health, and thus, have lower NLR values.…”
Section: Discussioncontrasting
confidence: 84%
“…Other studies in healthy humans have found that NLR is moderately heritable (36%) [4], differs as a function of racial disparities in the United States population [2], and that males have higher NLR than females [4] . Average NLR ranges from 1.5 to 2.8 in humans, with reference ranges between 1.1 and 4.5 [1-6].…”
Section: Introductionmentioning
confidence: 99%
“…41 Although PLR has been shown to be associated with prognosis of lung cancer in previous studies, studies on a predictive role of PLR in development of lung cancer are currently limited. [29][30][31][32] Previous studies reported a sex difference in PLR, with higher PLR in women than in men, 42,43 but studies address sex differences in the relationship between PLR and lung cancer risk are scarce. Although the mechanisms of sex-related differences in PLR are not fully understood, several factors, such as estrogen and low iron saturation in menstruating women, may affect platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…The data collected was entered in Microsoft Excel and analysed using SPSS V. 16. Descriptive analysis was done by calculating frequencies and proportions.…”
Section: Resultsmentioning
confidence: 99%
“…The mean NLR across all ages in men and women was 1.63 and 1.66, respectively. 16 The association of neutrophilic leucocytosis with bacteraemia and lymphocytosis with viremia is well known. 13 In the current study, the NLR was found to be higher in patients with bacterial infection compared to those with viral infection.…”
Section: Discussionmentioning
confidence: 99%